The Unwanteds - McMann, Lisa. (New York : Aladdin, 2011)
In a society that purges thirteen-year-olds who are creative, identical twins Aaron and Alex are separated, one to attend University while the other, supposedly Eliminated, finds himself in a wondrous place where youths hone their abilities and learn magic.
Keywords: Fantasy; Creative ability -- Fiction; Magic -- Fiction; Brothers -- Fiction; Twins -- Fiction